The role of the knowledge economy in the development of banking services in Libya - Alhasadi, Aza Yousef; Demirel, Yavuz (Center for Strategic Studies in Business and Finance SSBFNET, 2020)
The study focuses on the basic variables of the knowledge economy, where aims to know the role of the knowledge economy in the banking sector and solving the problems facing Libyan commercial banks in the development of banking services. In order to achieve the main purpose of the study, we used the descriptive-analytical method, by using the questionnaire. Where we surveyed a total of 320 employees at six commercial banks operating in the eastern region of Libya. Through incoming questionnaires, we have analyzed 299 questionnaires. The results of the analysis showed a positive relationship between the knowledge economy and the development of banking services and that the knowledge economy plays an active role in the development of banking services, as the sub-variables of the knowledge economy are knowledge, skills, education, IT infrastructure, speed, access to service, research and development, Innovation, institutional regime, economic incentives as well as the sub-dimensions of the developing of banking services that represented in online banking, data transfer services, the use of technology, and customer relations. all of them show a high positive relationship among them. Also, the study includes information on whether there are differences between the knowledge economy and the development of banking services in the banks included in the research. The results of the study showed that knowledge, skills, training, economic incentives, and institutional regime vary according to banks
Keywords: 9. Industry and infrastructure; 8. Economic growth